Case Report: Acute Eosinophilic Myocarditis With a Low-Flow Heart Failure With Preserved Ejection Fraction Phenotype - Aota, Hiroto; Yamamoto, Hiroyuki; Isogai, Jun; Imanaka-Yoshida, Kyoko; Hiroe, Michiaki; Tanaka, Takahiro (Frontiers in Cardiovascular Medicine, 2021)
Eosinophilic myocarditis is a rare subtype of myocarditis characterized by myocardial eosinophilic infiltration, and it is potentially fatal if left untreated. Although endomyocardial biopsy (EMB) is a cornerstone for the histological diagnosis of acute eosinophilic myocarditis (AEM), as it is an invasive procedure and has a low diagnostic accuracy, the diagnosis of AEM with hemodynamic instability remains challenging. We describe a case of AEM presenting as low-flow heart failure with preserved ejection fraction (HFpEF), with rapid progression to cardiogenic shock. The constellation of peripheral eosinophilia, increased left ventricular wall thickness, and HFpEF raised the suspicion of AEM. Contrast-enhanced computed tomography (CT) scan revealed heterogeneous hypoenhancement localized in the basal-to-mid septal and mid anterolateral walls of the left ventricle, strongly suggestive of acute inflammation. Based upon these findings, we performed CT-guided EMB, which lead to a definitive diagnosis. Subsequent high-dose corticosteroids allowed a rapid and dramatic recovery and normalization of cardiac structure and function. This case highlights the clinical importance of assessing AEM as a rare cause of HFpEF and the usefulness of CT-guided EMB in patients with hemodynamic instability.